Teachers’ Insights into the Efficacy of the ‘Reading Circle’ Project Using English Language Teaching Graded Readers - Inga Linde; Linda Daniela (Education Sciences)
The Sustainable Development Goals Report 2024, published by the United Nations, highlights quality education as a priority goal, emphasising its essential role in facilitating the achievement of other goals. Although there has been modest progress since 2019, several areas require further advancement, including the development of reading skills. Extensive reading plays an important role in foreign language acquisition, as it not only significantly enhances students’ vocabulary, text comprehension, reading, speaking, and writing skills, but also fosters the development of sustainable learning and self-regulated learning skills. In order to substantially increase students’ reading opportunities, the ‘Reading Circle’ (RC) project was initiated, allowing teachers and their students to read five to eight graded readers during English as a Foreign Language (EFL) classes throughout the school year. During the school year 2023/2024, 45 teachers and 1328 students of Grades 3–11 participated in the 9-month project. The aim of this study was to analyse teachers’ perceptions on the efficacy of the ‘Reading Circle’ project and the most common teaching techniques. The data indicate that the most commonly used teaching techniques across all levels of language learning were the text discussions and the completion of ready-made exercises, while a significant difference across the levels emerged in the techniques of students reading aloud versus reading silently. The findings of this study reveal that teachers highly evaluated the benefits of the project and observed positive improvements in students’ reading motivation, text comprehension, and advancements in their reading and speaking skills, and the outcomes imply that the ‘Reading Circle’ project is an effective method of enhancing sustainable learning and self-regulated learning skills.